(untitled) (Health Renaissance, 2011)
Objectives: To find the child sex ratio in the urban slum and elite area of Nagpur and also to compare child sex ratio according to birth order and sex of previous born child. Methods: The study involved house to house interview of mothers of 0-6 years children from urban slum and elite area of Nagpur city. Information regarding all children born in last 6 years, their date of birth, birth order, sex, interval between two births and information regarding any abortions were noted. Results: Child sex ratio was 934 females per 1000 males combined for both areas. Child sex ratio was significantly low (P<0.05) in elite area (904 females per 1000 males) compared to slum area (964 females per 1000 males). Child sex ratio was highest for Hindus (1051 in slum area and 975 in elite area) and lowest for others (778 in slum area and 375 in elite area). Child sex ratio decreases, as education of mother increases, except when mother was graduate or postgraduate for both areas combined upto birth orders three, child sex ratio was 941 females per 1000 males (981 for slum area and 904 for elite area). In elite area, for the second birth order, number of males was significantly higher than females, when first-born child was female (P<0.05). There was significant difference between number of males and females of second birth order, when the first-born child was male compared to when it was female (P<0.001). Conclusion: There is missing of girl child form the second and subsequent birth order, especially when the previous born child is female, which is more evident in elite area. Keywords: Child sex ratio; urban slum; elite area; birth order; India. DOI: http://dx.doi.org/10.3126/hren.v9i3.5589 HR 2011; 9(3): 189-193